Refleksi Keterampilan Manajerial, Komunikasi Interpersonal dan Budaya Mutu Berfokus pada Perilaku Anggota Organisasi (Organizational Citizenship Behavior) - Ganjar Winata (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
The objectives of the research was to determine the direct effect of managerial skill, interpersonal communication and quality culture toward organizational citizenship behavior (OCB) of teachers at public elementary school in North Lampung regency. The research method was a quantitative approach with survey and path analysis technique. The data was collected by distributing questionnaires to 205 teachers as samples from the target population of 419 teachers. Sampling technique was a proportional random. Data was analysed using descriptive and inferential statistics. The results of the research were: (1) managerial skill, interpersonal communication and quality culture had a direct positive effect toward organizational citizenship behavior. Based on the result, the effect of managerial skill, interpersonal communication and quality culture toward OCB was 0.651. It meant that 65.1 % of OCB variable was effected directly by managerial skill, interpersonal communication and quality culture, simultaneously; (2) managerial skill had a direct positive effect toward quality culture and interpersonal communication. The result calculated that quality culture variable was effected directly by managerial skill variable in as much as 49.28 %. Therefore, increasing organizational citizenship behavior could be carried out by improving managerial skill, interpersonal communication and quality culture.